(untitled) (Revista Apotheke, 2021)
This text investigates the popular cultural manifestation of Nego Fugido, its relations with the history of Brazil and how it affects the fishing community of Acupe, state of Bahia, where the event is being held. We present a description of the event, they’re symbolic elements, as they stand out in the character’s costumes, the processes that involve this movement movement in the narrative itself and that are mixed in the stories and legends of the residents. From experience lived in the event, records and sketches in drawing were made, during and after the presentation which split into artistc prodution that reflect the expressiveness of the event. The research generates a reflection on the concepts of identity and tradition that permeate the movement, as well as the factors of vigilance and power relations present in each represented character. Furthermore, it highlights the important role of memory in the lived experiences that become significant throughout life, serving as propelling springs for the creative process in the field of Visual Arts.